Chapter 10 Places of Belonging, Places of Detachment Belonging and Historical Consciousness in Narratives of Rural Finnish Girls - Vehkalahti, Kaisa (Bristol University Press, 2022)
Chapter 10 of this ePDF is available Open Access under CC-BY-NC-ND licence. This interdisciplinary collection charts the experiences of young people in places of spatial marginality around the world, dismantling the privileging of urban youth, urban locations and urban ways of life in youth studies and beyond. Expert authors investigate different dimensions of spatiality including citizenship, materiality and belonging, and develop new understandings of the complex relationships between place, history, politics and education. From Australia to India, Myanmar to Sweden, and the UK to Central America, international examples from both the Global South and North help to illuminate wider issues of intergenerational change, social mobility and identity. By exploring young lives beyond the city, this book establishes different ways of thinking from a position of spatial marginality.